P579 Online Education Significantly Improved Gastroenterologists' Knowledge of Treatment Options and Therapeutic Goals in Ulcerative Colitis. (27th May 2021) - Bell, E; Calle, M; Vermeire, S
Abstract: Background: With the rapid evolution in treatment strategies and the increasing range of available therapeutics for ulcerative colitis (UC), keeping pace with advances can be a challenge for busy physicians. We assessed whether online CME can improve gastroenterologists' knowledge of therapeutic goals and treatment options in UC. Methods: Gastroenterologists participated in an online CME activity entitled 'Management of UC: Expert Insights on Current and Emerging Therapies'. This was a 30-minute video roundtable discussion with accompanying slides. Educational effect was assessed using a repeated-pair design, pre-/post-assessment. A Chi-square test of independence determined if a statistically significant improvement (5% significance level, P <.05) existed in the number of correct responses between the pre-test and post-test scores. Cramer's V estimated the effect size of the education (<.06, modest impact; .06-.15, noticeable impact; .16-.26, considerable impact; >.26, extensive impact). The activity launched on 21 November 2019 with data collection through 4 February 2020. Results: Significant improvement in average percentage of correct responses, rising from 67% at baseline to 77% post-activity ( P <.001) and noticeable educational impact (Cramer's V=0.113) The percentage of gastroenterologists (n=232) answering all 3 questions correctly rose from 32% at baseline to 55% post-activity Significant improvements in knowledge of the minimum therapeutic goal for a patient with moderate-to-severe UC ( P <.01) and the VTE risk associated with treatments for UC ( P <.01) Numerical improvement in knowledge of clinical data from the UNIFI trial for ustekinumab in moderate-to-severe UC Almost half (44%) of gastroenterologists indicated improved confidence in their ability to describe clinical data for emerging biologic agents in UC Conclusion: Online education, delivered as a 30-minute video roundtable discussion among experts, significantly improved gastroenterologists' knowledge of therapeutic goals and treatment options in UC, which should equip them with the knowledge to make more informed choices for their patients. The success of this online activity, particularly with regard to the impressive improvement in confidence, suggests that gastroenterologists would benefit from further education to reinforce not just their knowledge of clinical data for novel agents but also their confidence in using these new agents to manage patients with UC.